Dosiomics in the analysis of medical images and prospects for its use in clinical practice - Vladimir A. Solodkiy; Nikolay V. Nudnov; Mikhail E. Ivannikov; Elina S-A. Shakhvalieva; Vladimir M. Sotnikov; Aleksei Yu. Smyslov (Digital Diagnostics, 2023)
BACKGROUND: In recent years, there has been a notable increase in the number of articles using the term “dosiomics”. However, there are no literature reviews on this topic in the Russian language.